ExermiR‐129‐3p Enhances Muscle Function by Improving Mitochondrial Activity Through PARP1 Inhibition - Yeo Jin Shin; Jae Won Yang; Heeyeon Jeong; Joyeong Kim; Bora Lee; Ji‐Won Kim; Seung‐Min Lee; Ju Yeon Kwak; Young Hoon Son; Kap Jung Kim; Yong Ryoul Yang; Chuna Kim; et al. (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Physical exercise has beneficial effects on various organs, including skeletal muscle. However, not all patients are capable of engaging in exercise to maintain muscle function, which underscores the importance of identifying molecular mechanisms of physical training that could lead to the discovery of exercise‐mimicking molecules. Methods This study sought to identify molecular mediators of exercise that could improve muscle function. We focused on the exercise‐induced microRNA (miR)‐129‐3p, investigating its role and effects on mitochondrial activity both in vivo and in vitro. The expression of miR‐129‐3p was analysed in skeletal muscle following exercise, and its downstream effects on the poly (ADP‐ribose) polymerase‐1 (Parp1)‐SIRT1‐PGC1α signalling pathway were elucidated. Functional studies were conducted using muscle‐specific overexpression of miR‐129‐3p in adult mice and intramuscular injection of AAV9‐miR‐129‐3p in obese mice to assess exercise capacity and muscle strength. Results Exercise was found to upregulate miR‐129‐3p in skeletal muscle (p < 0.05), which directly inhibits Parp1, a major NAD+‐consuming enzyme. This inhibition leads to increased NAD+ levels (p < 0.05), activating SIRT1 and subsequently reducing the acetylation of PGC1α, thereby enhancing mitochondrial function. Muscle‐specific overexpression of miR‐129‐3p in adult mice significantly enhanced exercise capacity (> 130%, p < 0.0001), while AAV9‐miR‐129‐3p injections ameliorated muscle weakness (twitch force, > 140%, p < 0.05; tetanic force, > 160%, p < 0.01) in obese mice. In human skeletal muscle myoblasts, miR‐129‐3p improved mitochondrial function via the PARP1‐SIRT1‐PGC1α signalling pathway. Conclusion Our findings suggest that miR‐129‐3p, induced by exercise, can mimic the beneficial effects of physical exercise. This highlights miR‐129‐3p as a potential therapeutic target for improving muscle health, especially in individuals unable to exercise.